Pengaruh Ketidaklayakan Gaji terhadap Beban Kerja Mental Melalui Kepuasan Kerja pada Pegawai Paruh Waktu di SMPN 2 Dompu - Hendra Ferdiansyah; Samsudin; Firmansyah (LPPM STIEM BONGAYA, 2026)
This study aims to examine the effect of inadequate wages on mental workload through job satisfaction as a mediating variable among part-time employees at SMPN 2 Dompu. Using a quantitative approach, this study involved a population and a saturated sample of 31 part-time employees at the institution. Research data were obtained through field observations and the distribution of a Likert-scale questionnaire, which were subsequently analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method via SmartPLS 3.0 software. The results of the data analysis demonstrate that inadequate wages have a direct, positive, and significant effect on both mental workload and employee job satisfaction. Furthermore, job satisfaction was found to have a positive and significant effect on mental workload and was able to positively and significantly mediate the relationship between inadequate wages and mental workload. It can be concluded that disproportionate compensation triggers a decline in job satisfaction, which ultimately exacerbates the accumulation of employees’ mental workload; therefore, an evaluation and improvement of wage allocation by school management and relevant local government agencies are strongly recommended to maintain educators’ well-being and cognitive stability.